1981
DOI: 10.1007/bf02110028
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic production of placenta-“specific” tissue proteins (PP5 and PP11) by malignant breast tumors

Abstract: With use of an enzyme-bridge immunoperoxidase (PAP) technique, an immunohistochemical localization of the two new placenta-"specific" tissue proteins, PP5 and PP11, was investigated in 16 cases of breast cancer. PP5 was localized in the cytoplasm of breast cancer cells in 62.5% of cases examined and PP11, in 46.7%. Thus PP5 and PP11 may be markers for breast cancer and the detection of these proteins in sera from breast cancer patients may be more reliable and useful in the detection and monitoring of breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Differences in the intracellular protein composition of the tissues analyzed may account for this observation that also indicates an easier separation of contaminating proteins from 17bHSD1 in breast tissue than in placenta. This hypothesis is supported by electrophoresis in our study, showing a considerably reduced amount of proteins in mammary Sup2 compared to placenta, but also by others having demonstrated the absence of a variety of placental proteins in normal breast tissue 42 . Our study revealed a non-significant inhibitory effect of testosterone on 17bHSD1 activity in both, placenta and breast tissue.…”
Section: Discussionsupporting
confidence: 88%
“…Differences in the intracellular protein composition of the tissues analyzed may account for this observation that also indicates an easier separation of contaminating proteins from 17bHSD1 in breast tissue than in placenta. This hypothesis is supported by electrophoresis in our study, showing a considerably reduced amount of proteins in mammary Sup2 compared to placenta, but also by others having demonstrated the absence of a variety of placental proteins in normal breast tissue 42 . Our study revealed a non-significant inhibitory effect of testosterone on 17bHSD1 activity in both, placenta and breast tissue.…”
Section: Discussionsupporting
confidence: 88%
“…Detection of PP11 in several malignant cells (3)(4)(5) can instead suggest that its deregulated expression may be associated with oncogenesis. In this regard, we find intriguing the parallel between the physiological expression of PP11 in syncytiotrophoblastic cells and its aberrant expression in tumoral cells; both cell types are characterized by the capacity to invade the adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was shown that the placenta-specific proteins were also expressed in several tumor tissues; PP11 was detected in 66.7% of the analyzed mucinous cystadenocarcinomas and in 57.1% of serous cystadenocarcinomas tested, whereas it was not found in normal ovaries (3). Moreover, PP11 was also found in 47% of all breast cancers examined (4) and in 38% of all testicular and gastric cancers studied (5). These results suggested that this protein may be involved in carcinogenesis and, therefore, may represent a suitable molecular marker for tumor diagnosis.…”
mentioning
confidence: 99%
“…Inaba et al have investigated the localization of PP5, PP10, PPll, and PP12 in trophoblastic tumors and ovarian adenocarcinomas by using immunohistochemical methods [9,11,13,14]. These proteins have been found to be associated with the carcinoma of the breast and digestive system [3,10,12,15]. Serum levels of PP7 and PP8 were relatively high in the cases with hematological malignancy, and cancer of the digestive and the respiratory system [2].…”
Section: Introductionmentioning
confidence: 97%